1997
DOI: 10.1002/(sici)1099-1573(199703)11:2<155::aid-ptr48>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Some Isoquinoline Alkaloids from Argemone mexicana on Electrically Induced Contractions of Isolated Guinea‐pig Ileum

Abstract: The present study examines the effects of the extracts [petroleum ether, CHCl 3 , CHCl 3 /MeOH (9:1) and MeOH], partially purified fractions and pure compounds from Argemone mexicana on the electrically induced contractions of the isolated guinea-pig ileum (E.C.I.).The results of the experiments indicate that CHCl 3 /MeOH (9:1) and MeOH extracts, tested at a concentration of 400, 200 and 100 g/mL, dose-dependently reduced the guinea-pig ileum contractions, whereas the petroleum ether and CHCl 3 extracts did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Furthermore, a large proportion of the contraction in opioid withdrawal in vitro is due to Ach release since it is blocked by atropine or hyoscine (Tsou et al, 1982;Chal, 1983). A relationship between cholinergic and protopine alkaloids has been reported by Ustunes et al (1988) and Piacente et al (1996) indicating anticholinergic properties for these alkaloids.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, a large proportion of the contraction in opioid withdrawal in vitro is due to Ach release since it is blocked by atropine or hyoscine (Tsou et al, 1982;Chal, 1983). A relationship between cholinergic and protopine alkaloids has been reported by Ustunes et al (1988) and Piacente et al (1996) indicating anticholinergic properties for these alkaloids.…”
Section: Resultssupporting
confidence: 80%
“…Although the aerial parts of A. constricta are empirically used in folk medicine as anthelmintics, emmenagoguse and against the snake bites (Montes and Wilkomirsky, 1985), there are no data in the literature on the possible pharmacological effects. Recently, we have isolated and characterized five new protopine-type alkaloids from the aerial parts of Aristolochia constricta (Rastrelli et al, 1997) and the pharmacological study performed with these new protopine alkaloids indicated that they possess anticholinergic activity (Rastrelli et al, 1997) thus confirming the previous paper on protopine alkaloids (Ustunes et al, 1988;Piacente et al, 1996). Recently, we have demonstrated that some protopine alkaloids from Argemone mexicana were able to reduce significantly morphine withdrawal in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Capasso and his group (1997) studied the effect of the methanolic extract, its partially purified fraction, and the isolated pure compounds such as protopine (9) and allocryptopine (10) from A. mexicana on the morphine withdrawal effect in guinea pig isolated ileum; all the tested materials were observed to reduce the effect significantly and in a concentrationdependent manner, thereby suggesting the possible application of isoquinoline alkaloids as potential agents in the treatment of drug abuse. Further investigation in this direction also indicated that that CHCl 3 /MeOH and MeOH extracts reduced the contractions of isolated guinea-pig ileum in a dose-dependent manner (Piacente et al, 1998); the effects were attributed to the active compounds identified as protopine (9), allocryptopine (10) and berberine (2).…”
Section: Effect On Ileum Organmentioning
confidence: 92%
“…Biological activity Reference berberine (2) Anti-fertility activity Effect on ileum contraction in guinea pig Antimalarial activity Gupta et al, 1990Piacente et al, 1998Avello Simoes Pires, 2009 dehydrocorydalmine (4) Antifungal activity Singh et al, 2009a (+)-reticuline (8) Cytotoxic activity Chang et al, 2003a protopine (9) Anti-fertility activity Effect on ileum in guinea pig Mollucicidal activity Antimalarial activity Gupta et al, 1990Capasso et al, 1997Piacente et al, 1998Avello Simoes Pires, 2009 allocryptopine (10) Effect on ileum in guinea pig Antimalarial activity Capasso et al, 1997;Piacente et al, 1998Avello Simoes Pires, 2009 chelerythrine (22) Cytotoxic activity Chang et al, 2003a sanguinarine (23) Mollucicidal activity (+)-argenaxine (27) Cytotoxic activity Chang et al, 2003a (+)-higenamine (28) Cytotoxic activity Chang et al, 2003a oxyberberine (32) Antifungal activity Singh et al, 2009a N-demethyloxysanguinarine (33) Cytotoxic activity Chang et al, 2003a pancorine (34) Cytotoxic activity Chang et al, 2003a (±)-6-acetonyl dihydrochelerythrine (38) Anti-HIV activity Chang et al, 2003b angoline (41) Cytotoxic activity Chang et al, 2003a dihydropalmatine hydroxide (44) Anti-fertility activity Gupta et al, 1990 β-amyrin (47) Anti-inflammatory & analgesic activity Sukumar et al, 1984 cysteine (66) Anti-inflammatory & analgesic activity Sukumar et al, 1984 phenylalanine (67) Anti-inflammatory & analgesic activity Sukumar et al, 1984 isorhamnetin-3-O-β-D-glucopyanoside (70) Anti-inflammatory & analgesic activity Sukumar et al, 1984 intraperitoneally administered 0.5, 1.0, 2.0 and 4.0 mL/kg body weight of the oil to analyze chromosome aberrations and micronucleus test, while 0.25, 0.5, 1.0 and 2.0 mL/kg body weight were given for alkaline comet assay. The frequencies of chromosomal aberrations and micronucleated erythrocytes formation in mouse bone marrow cells increased in a dose-dependent manner following the oil treatment.…”
Section: Compoundmentioning
confidence: 99%
“…Berberine Anti-fertility activity Effect on ileum contraction in guinea pig, Antimalarial activity [18,19,20,21,22] Apigeal parts Allocryptopine Effect on ileum in guinea pig Antimalarial activity [20,21] Seeds Sanguinarine Mollucicidal activity [23,21] Solanum xanthocarpum Fruit Saponins Function in stimulation of Heart [24] Fruit Solanacarpine, solamargine, caffeic acid coumarins, aesculetin and aesculin…”
Section: Argemone Mexicana Apigeal Parts Seedsmentioning
confidence: 99%